2013
DOI: 10.1136/heartjnl-2012-303237
|View full text |Cite
|
Sign up to set email alerts
|

Miscarriage and future maternal cardiovascular disease: a systematic review and meta-analysis

Abstract: ContextThe 2011 American Heart Association guidelines identified pregnancy complications as a risk factor for cardiovascular disease in women. However, miscarriage was not mentioned within the guidelines, and there is no consensus on the association between miscarriage and future risk of cardiovascular disease.ObjectiveTo confirm or refute the association, a meta-analysis of published papers was conducted.Data sourcesPubMed, Web of Knowledge and Scopus were systematically searched to identify appropriate artic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
92
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(101 citation statements)
references
References 48 publications
5
92
0
2
Order By: Relevance
“…These findings support the plausibility of direct biological mechanisms being involved, and are well-aligned with previous studies demonstrating that the magnitude of the risk of maternal CVD increases with the number and/or recurrence of other pregnancy complications, including hypertensive pregnancies [26], preterm birth [27], and miscarriage [3]. The most compelling study is a meta-analysis that showed the association of recurrent miscarriage with future maternal CVD was stronger than the association of single miscarriage (pooled odds ratios = 1.99 versus 1.45) [3].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…These findings support the plausibility of direct biological mechanisms being involved, and are well-aligned with previous studies demonstrating that the magnitude of the risk of maternal CVD increases with the number and/or recurrence of other pregnancy complications, including hypertensive pregnancies [26], preterm birth [27], and miscarriage [3]. The most compelling study is a meta-analysis that showed the association of recurrent miscarriage with future maternal CVD was stronger than the association of single miscarriage (pooled odds ratios = 1.99 versus 1.45) [3].…”
Section: Discussionsupporting
confidence: 90%
“…A range of socioeconomic, behavioural, and biological risk factors shape the distribution and development of CVD. In addition to established risk factors shared by both men and women (e.g., smoking, hypercholesterolaemia, hypertension), complications during pregnancy (including preeclampsia [2], miscarriage [3], preterm birth [4] and low birth weight or fetal growth restriction [5]) have been identified as gender-specific risk factors that may help identify women who are susceptible to premature CVD. This evidence is emerging in parallel with the increased appreciation of the burden of CVD in women [6], including in women aged 18-44 years, in whom CVD is the third leading cause of death [7].…”
Section: Introductionmentioning
confidence: 99%
“…Observational studies suggest that women with a history of RM also have an increased risk of CVD 6, 7, 8, 9. Several hypotheses are possible for the association between both diseases; shared common risk factors such as obesity and smoking,10 endothelial dysfunction,11 and a genetic predisposition is assumed 12…”
Section: Introductionmentioning
confidence: 99%
“…The relation between pregnancy loss and incident CVD has been evaluated using several study designs 35. Even though the prevalence of posttraumatic stress disorder after miscarriage and stillbirth is similar,6, 7 several studies suggest that CVD may have a stronger association with stillbirth than with miscarriage.…”
Section: Discussionmentioning
confidence: 99%